Analisis Kesesuaian Materi Protista pada Buku Teks dengan Kompetensi Dasar Kurikulum 2013 - Anna Rahmayanti; Tri Jalmo; Berti Yolida (Universitas Lampung, 2018)
This study aims to describe the conformity level of protist material on Biology textbook of high school class X with basic competence of 2013 curriculum from aspect of material breadth and depth. This study using descriptive design. The book sample used was book A published by Erlangga and book B published by Yrama Widya. The data in this study was the suitability of protist material on textbook based on the aspect of material breadth and depth. Data were collected using documentation studies through content analysis of the book. The result of this study showed that the conformity level of protist material with the basic competence of 2013 curriculum on A book was evaluated from the breadth aspect of material that was categorized